Artificial Intelligence as a Catalyst for Transforming School Leadership Practices - Egwu, Joyce Uche; Osegbue, Gloria Chineze (Teaching, Learning, and Development, 2026)
Modern school administration faces growing demands for efficiency, data-driven decision-making, inclusive leadership, and continuous improvement in learning outcomes. However, many school leaders continue to rely on traditional, manual practices that limit timely insights and create inefficiencies in planning, monitoring, staffing, and communication, particularly in resource-constrained systems. This study employed a descriptive survey design to examine the use of artificial intelligence (AI) in school leadership. The sample comprised 60 school leaders from public tertiary institutions in Anambra State, purposively selected to represent different levels of experience (22 males and 38 females). Data were collected using a structured online questionnaire administered via Google Survey, covering AI utilization, its influence on decision-making, barriers to adoption, and its role in leadership transformation. Findings indicated that AI was moderately to highly utilized, primarily for communication and administrative tasks. The impact of AI on decision-making was moderate, particularly in enhancing reliance on data-based information and reducing error. Major barriers to adoption included limited training, inadequate funding, technical challenges, and staff resistance. AI was perceived as a driver of organizational change, especially in improving operational efficiency and leadership practices. ANOVA results revealed a statistically significant effect of AI on decision-making and organizational change (p < 0.05), while prior AI usage and perceived difficulties were not statistically significant (p > 0.05). The study concludes that AI holds strong potential to transform school leadership and emphasizes the need for capacity building, technological investment, and ethical guidelines to support effective AI integration in education.